FROM SURRENDER STORIES TO PERSISTENCE STORIES: YOUNG GIRLS’ NARRATIVES OF AGENCY AND POWER IN CHILD–PARENT CONFLICTS - Lahtinen, Maria; Sevón, Eija; Böök, Marja Leena (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
This paper examines the dynamics of agency and power as revealed in young girls’ fictional narratives about child–parent conflicts that are caused by incompatibility between the goals of children and parents in everyday family life. The data were collected from 26 girls aged 4 to 6 using the Story Magician’s Play Time method. Narrative analysis yielded five types: mediation and compromise stories, surrender stories, persistence stories, solidarity stories, and standoff stories. In the girls’ stories, agency and power were multifaceted and variable phenomena that were negotiated in a relational context in which the gender of the child and parent characters played an important role. Power relations tended to be narrated as more hierarchical and immutable in child–father conflicts, and more often as negotiated in child–mother conflicts. However, when narrated as deploying unyielding and tactical actions, the child characters were only able to exert power over the parent in girl–mother conflicts. Thus, some stories conveyed a clear, hierarchical generational order while others demonstrated children’s agentic power to reshape adult dominance in child–adult conflicts in diverse ways. The practical implications of the findings are also discussed.